Ellenchos Practices in Classical Islam: Hayy b. Yaqzan of Ibn Tufayl - Faried F. Saenong (IJMIS: Istiqlal Journal on Mosque and Islamic Studies, 2024)
Scholars have considered the story of Robinson Crusoe by Daniel Defoe (1660-1731) in Western context as equally comparable to that of Hayy b. Yaqzan by Ibn Tufayl (1110-1185) in Islamic philosophy, or vice versa. Both imaginative and allegorical tales feature different fictive figures who lived alone in a remote island. They both covers how human being could absorb divine and profane knowledge based on their own experience with particular level of intellectuality and intention of knowledge seeking. Both tales also stand for the way both authors, followed later by many writers and novelists, employed imagination and allegories to reconstruct ellenchos to emphasise lessons learned and wisdoms from both stories. Although both Ibn Tufayl and Defoe practiced assorted styles and methods in different time and cultural contexts, both have set trends in writing such imaginative and allegorical stories in world literature. This paper examines the practices of ellenchos in classical Islam, by taking the case of “Hayy b. Yaqzan” by Ibn Tufayl. Starting with a postulation that the fundamental difference between Islamic philosophy and Western one is at the starting line of neo-platonism, this paper reorients the understanding of Ibn Tufayl’s philosophical contribution that is peripheral in Islamic philosophy. It includes his neo-platonist orientation which is the general alignment of Muslim philosophers.